The conservation value of secondary vegetation for Fijian woodland birds. (3rd July 2019) - Reid, Elizabeth; Naikatani, Alivereti; Keppel, Gunnar; Kleindorfer, Sonia
ABSTRACT: Half of Fiji's 66 land bird species are endemic and 15 species are threatened with extinction following ~70% deforestation. Under conditions of large-scale habitat loss, secondary vegetation can be important for woodland biodiversity conservation. This study compares avian abundance and diversity in secondary vegetation on Viti Levu, Fiji. We use avian point surveys at replicate sites in regenerating mahogany plantation (Colo-i-Suva; eastern lowlands), regenerating native forest (Koroyanitu National Heritage Park; western highlands) and grassland (Koroyanitu National Heritage Park). We ask if there are differences in avian abundance and species richness across habitat types. In total, we recorded 1063 birds from 33 bird species. Regenerating forest sites had the greatest species richness with mostly endemic and native woodland bird species and few introduced species. Regenerating plantation sites harboured a comparable number of endemic species and threatened species as regenerating forest sites but had significantly fewer native species and no introduced species. We recorded the most birds at grassland sites as well as the most introduced species. The findings of this study underscore the importance of regenerating native forest and regenerating plantation as habitats for Fiji's endemic woodland birds. Increasing the expanse of regenerating forest sites should be considered for conservation planning to sustain Fiji's extant birds.